A data association model for analysis of crowd structure - Zitouni, Sami M.; Śluzek, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
The paper discusses a non-deterministic model for data association tasks in visual surveillance of crowds. Using detection and tracking of crowd components (i.e., individuals and groups) as baseline tools, we propose a simple algebraic framework for maintaining data association (continuity of labels assigned to crowd components) between subsequent video-frames in spite of possible disruptions and inaccuracies in tracking/detection algorithms.
Keywords: data association; visual surveillance; crowd analysis; algebraic model